(untitled) (AYUSHDHARA, 2017)
According to classical literature of Unani Medicine, management of any disease depends upon the diagnosis of disease. In the diagnosis, clinical features, i.e., signs, symptoms, laboratory investigations and Mizaj (temperament) are important. Any cause or factor is countered by Quwwat Mudabbira lil-Badan (medicatrix naturae: the power of body responsible to maintain health), the failing of which may lead to quantitatively or qualitatively derangement of the normal equilibrium of Akhlat (humors) of body which constitute the tissues and organs. After diagnosing the disease, Usul-e-Ilaj (principle of treatment) of disease is determined on the basis of etiology. The principle of management is decided which may be one or more of the four types of treatment lines such as Ilaj bil-Tadbeer (Regimental therapy), Ilaj bil-Ghiza (Diet therapy), Ilaj bil-Dawa (Pharmacotherapy), Ilaj bil-Yad or Jarahat (Surgery). Ilaj bil-Tadbeer is most preferred one. Dalk is one of the most important parts of Ilaj bil-Tadbeer. Details about Dalk have been mentioned in Unani Literature, some of them are described in this paper.